New American streamline - Destinations (An intensive American English series for avanced students: Student Book) - Bernard Hartley (Oxford Univ. Press, 1996)
This book is designed to follow "Departures" and "Connections", consolodating and building upon the oral skills. The material consists of 80 units, each clearly laid out on a separate page